Avaliação estatística das variáveis relacionadas a qualidade de farelo de soja para frangos de corte - Jardim, Mihayr Morais (2019)
The use of soybean meal for poultry presents restrictions due to the antinutritional factors when poorly processed. The objective of this work was to discuss a literature review on soybean meal quality and to evaluate the available database on soybean meal quality relating thermal processing with bromatological quality for poultry nutrition. The first chapter was about the effect of processing and quality of soybean meal, in chapter two and three were evaluated analysis database on wet chemistry and Near Infrared Spectroscopy (NIRS), respectively. For the composition of chapter two, the 283 samples were obtained from a chicken producer integrating company located in the state of Goiás. In the first stage, there was categorization of bran samples by KOH-soluble protein levels: below 75%, from 75%. 80%, 80% to 85%, 85% to 90%, and above 90%. After categorization, multivariate analyzes and ANOVA with Scott Knott test were performed to compare the means. Step two categorized the analysis results by level of urea activity, classifying the 283 samples into 5 categories: 0; 0.01; 0.011-0.05; 0.051-0.1 and above 0.1. Multivariate analyzes and ANOVA were performed with Scott Knott test to compare the means. The third chapter was made with database of bran analysis via NIRS and statistical analysis was performed with nonparametric tests for amino acid and bromatological values compared with urease levels read in NIRS. In step 1 the data differed significantly for solubility in KOH, indicative of urea activity and only 1 group of soluble protein differed from a mean percentage of crude protein (% CP). In experiment two, the groups of urea activity differed statistically for protein solubility in KOH, urea activity. For groups of 0; and 0.01 of urea activity differed from the average of crude fiber. In chapter 3, experiment with database obtained via NIRS, there was a difference between the humidity and the highest values of urea activity; for the aminogram, we found statistical differences with nonparametric tests for cystine, methionine + cystine; Arginine, Isoleucine, Glycerin, Serine and Proline.